Q: Solve 8 - 3 over 4 - 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

To solve 2/3 + 4/6, find a common denominator by finding the least common multiple of 3 and 6, which is 6. Convert both fractions to have a denominator of 6, giving us 4/6 + 4/6. Add the numerators together to get 8/6. Simplify the fraction to its lowest terms to get 4/3. Therefore, 2/3 + 4/6 equals 4/3.

3 - 15/6 = 3 - 5/3 = (9-5)/3 = 4/3 = 1 and 1/3

3/9 reduces to 1/3 4/8 reduces to 1/2 6 is the LCM to solve: 1/3 = 2/6 1/2 = 3/6 Summing gives 5/6.

If you would to solve for (l) then l = 4x/2 + 3/2 (4x + 3 is over 2).To solve for x. x = 2l/4 + 3/4 ( 2l + 3 is over 4)Hope this helps.

4 over 1 is 4. 2 + 4 is 6.

Related questions

To solve 2/3 + 4/6, find a common denominator by finding the least common multiple of 3 and 6, which is 6. Convert both fractions to have a denominator of 6, giving us 4/6 + 4/6. Add the numerators together to get 8/6. Simplify the fraction to its lowest terms to get 4/3. Therefore, 2/3 + 4/6 equals 4/3.

3 - 15/6 = 3 - 5/3 = (9-5)/3 = 4/3 = 1 and 1/3

3/9 reduces to 1/3 4/8 reduces to 1/2 6 is the LCM to solve: 1/3 = 2/6 1/2 = 3/6 Summing gives 5/6.

2/3 +4/6 =

2/3 + 4/6 =4/6 + 4/6 =8/6 =4/3 or =1 1/3

5 7 --- = ---- 3+1 6 ________________ 5 7 --- = --- 4 6 _______________ 4*7 = 5*6 28 = 30 28=/=30 False equation

If you would to solve for (l) then l = 4x/2 + 3/2 (4x + 3 is over 2).To solve for x. x = 2l/4 + 3/4 ( 2l + 3 is over 4)Hope this helps.

4 over 1 is 4. 2 + 4 is 6.

3 and 2/3 is the same as 3 and 4/6.

5/6 - m/4 = 1/3. First isolate the variable m, start by adding m/4 to both sides. 5/6 = 1/3 + m/4. Then subtract 1/3 from each side. 5/6 - 1/3 = m/4. Next multiply both sides by 4. 4 ( 5/6 - 1/3 ) = m. Then solve for m. 4 ( 5/6 - 2/6 ) = m. 4 ( 3/6 ) = m 4 ( 1/2 ) = m 2 = m

4/6 = 2/3; therefore, 2/3 + 4/6 = 4/3.

6/4 or 3/23/4 + 3/4 = 6/4 or 3/2